Genome-wide identification of long non-coding RNA for Botrytis cinerea during infection to tomato (Solanum lycopersicum) leaves - Haojie Shi; Guijuan Ding; Yun Wang; Jiaqi Wang; Xiaoli Wang; Dan Wang; Ping Lu (BMC Genomics, 2025)
Abstract Long non-coding RNA (lncRNA) plays important roles in animals and plants. In filamentous fungi, however, their biological function in infection stage has been poorly studied. Here, we investigated the landscape and regulation of lncRNA in the filamentous plant pathogenic fungus Botrytis cinerea by strand-specific RNA-seq of multiple infection stages. In total, 1837 lncRNAs have been identified in B. cinerea. A large number of lncRNAs were found to be antisense to mRNAs, forming 743 sense-antisense pairs, of which 55 antisense lncRNAs and their respective sense transcripts were induced in parallel as the infection stage. Although small RNAs were produced from these overlapping loci, antisense lncRNAs appeared not to be involved in gene silencing pathways. In addition, we found the alternative splicing events occurred in lncRNA. These results highlight the developmental stage-specific nature and functional potential of lncRNA expression in the infection stage and provide fundamental resources for studying infection stage-induced lncRNAs.